Palmitoylethanolamide Reduces Formalin-Induced Neuropathic-Like Behaviour Through Spinal Glial/Microglial Phenotypical Changes in Mice - Luongo, Livio; Guida, Francesca; Boccella, Serena; Bellini, Giulia; Gatta, Luisa; Rossi, Francesca; de Novellis, Vito; Maione, Sabatino (CNS & Neurological Disorders - Drug Targets, 2013)
Palmitoylethanolamide (PEA) is an endogenous cannabinoid-like compound in the central nervous system, which can modulate several functions in different pathological states, such as inflammation and pain response. We have here investigated the effect of PEA (5-10 mg/kg, intraperitoneally) on mechanical allodynia and thermal hyperalgesia 3 and 7 days following peripheral injection of formalin. Formalin induced a significant decrease of thermal and mechanical threshold in the injected and contralateral paw. PEA chronic treatment (once per day) significantly reduced mechanical allodynia and thermal hyperalgesia in a dose-dependent manner. Consistently, in vivo electrophysiological analysis revealed a significant increase of the duration and frequency, and a rapid decrease in the onset of evoked activity of the spinal nociceptive neurons 7 days after formalin. PEA normalized the electrophysiological parameters in a dosedependent manner. Moreover, we investigated PEA effect on the glial/microglial phenotypical changes associated with spinal neuronal sensitization. We found that formalin induced a significant microglia and glia activation normalized by PEA, together with increased expression of glial interleukin 10. Finally, primary microglial cell cultures, conditioned with PEA or vehicle, where transplanted in naive and formalin-treated mice, and nociceptive neurons were recorded. We observed that only PEA-conditioned cells normalized the activity of sensitized nociceptive neurons. In conclusion these data confirm the potent anti-inflammatory and anti-allodynic effect of PEA, and highlight a possible targeted microglial/glial effect of this drug in the spinal cord.
Keywords: microglia